1995
DOI: 10.1111/j.1432-1033.1995.tb20812.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Escherichia Coli Cytochrome d by Low ΔH+ and by Sodium Ions

Abstract: Regulation of synthesis of cytochrome d in Escherichia coli has been studied using mutants with cytochrome‐d‐β‐galactosidase gene fusions. It was shown that various protonophorous uncouplers, when added to the growth medium, cause induction of the cytochrome d synthesis. The cytochrome‐d‐inducing activity of uncouplers correlates with their ability to inhibit such a ΔH+‐driven function as motility of the E. coli cells. An increase in the Na+ concentration in the growth medium from 1.5mM to 25mM results in indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The PMF (⌬p) has been proposed as a signal being sensed by the Arc system (2,30) as ArcAB-dependent induction of cytochrome bd synthesis has been observed in aerobically growing cells by the addition of protonophores and the inducing potency of the protonophores was found to be proportional to their uncoupling activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMF (⌬p) has been proposed as a signal being sensed by the Arc system (2,30) as ArcAB-dependent induction of cytochrome bd synthesis has been observed in aerobically growing cells by the addition of protonophores and the inducing potency of the protonophores was found to be proportional to their uncoupling activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since molecular oxygen has been excluded as the biochemical signal being sensed by ArcB (24,28,38), a number of other potential signals have been proposed, including intracellular metabolites (e.g., NADH, D-lactate, and pyruvate), the redox state of the respiratory chain, and the PMF (2,22,24,30). In this study we used steady-state chemostat cultures to investigate in detail the response of E. coli to varying oxygen availability.…”
mentioning
confidence: 99%
“…There have been reports that the cytochrome d terminal oxidase of E. coli is not an H ϩ pump (162) but a Na ϩ pump (6,8,15,135). An Na ϩ -transporting terminal oxidase has also been found in a representative of the genus Bacillus (8,115,178), later identified as Bacillus halodurans (71) (Table 1) but, rather, tentatively consider them to be H ϩ pumps (Table 2).…”
Section: ؉ -Transporting Terminal Oxidasesmentioning
confidence: 99%
“…Nevertheless, these oxidases clearly differ in induction conditions. The A. vinelandii bd-type oxidase is induced by an [02] increase whereas the E. coli enzyme is induced under conditions when protonic potential decreases [14], in particular by lowering the 02 concentration [15]. This is why Poole has suggested that the bd-type oxidases of ,4. vinelandii and E. coli perform different functions [8].…”
Section: Introductionmentioning
confidence: 99%